Seroprevalance of antibodies specific for severe fever with thrombocytopenia syndrome virus and the discovery of asymptomatic infections in Henan Province, China. - Yanhua Du; Ningning Cheng; Yi Li; Haifeng Wang; Aiguo You; Jia Su; Yifei Nie; Hongxia Ma; Bianli Xu; Xueyong Huang (Public Library of Science (PLoS), 2019)
Background Severe fever with thrombocytopenia syndrome (SFTS) is a severe emerging disease caused by SFTS virus (SFTSV), and the geographical distribution of SFTS has been increasing throughout China in recent years. To assess SFTSV-specific antibody seroprevalence, a cross-sectional study was conducted for healthy people in high SFTS endemic areas of Henan province in 2016. Methods This study used a stratified random sampling method to select 14 natural villages as the investigation sites. From April to May 2016, participants completed a questionnaire survey and serum samples were collected. All serum samples were subjected to ELISA to detect SFTSV-specific IgM and IgG. All IgM-positive samples were further tested by real-time RT-PCR, and isolation of virus from serum was attempted. Any participant who was IgM-positive was followed up with a month later to confirm health status. Results In total, 1463 healthy people participated in this study. The average seropositive rates for SFTSV-specific IgG and IgM were 10.46% (153/1463) and 0.82% (12/1463), respectively. IgM was detected in 12 individuals, and SFTSV RNA was detected in six of them. Virus was isolated from five of the six SFTSV RNA-positive individuals, and phylogenetic analyses revealed that all five isolates belonged to SFTSV group A. No IgM-positive participants exhibited any symptoms or other signs of illness at the one-month follow up. Conclusions This study identified a relatively high incidence of SFTSV-specific antibody seropositivity in healthy people in Xinyang city. Moreover, our data provide the first evidence for asymptomatic SFTSV infections, which may have significant implications for SFTS outbreak control.